Comparison between continuous and pulsed low-intensity laser on the healing of skin grafts applied to recently created wounds in rabbits (Oryctolagus cuniculus) - Reis Filho, Nazilton de Paula; Ferreira, Marília Gabriele Prado Albuquerque; Pascoli, Ana Lucia de Carvalho Rosa; Pazzini, Josiane Morais; de Paiva, Felipe Noleto [UNESP]; Ferrari, Bruno Santos; Floriano, Beatriz Peres; Moraes, Paola Castro [UNESP]; Ferraudo, Antonio Sergio [UNESP]; de Nardi, Andrigo Barboza [UNESP] (FapUNIFESP (SciELO), 2024)
Skin grafting is a simple and very useful surgical technique for wound repair, especially where there is difficulty in performing direct synthesis or other reconstructive techniques. low-intensity laser (LIL) has already been used successfully in cases where the graft was applied to wounds shortly after its creation. However, LIL still lacks standardization due to conflicting studies on its results. Thus, this study compared the effectiveness of continuous wave LIL with pulsed wave LIL in stimulating the healing of skin grafts, applied to newly created wounds in rabbits. For this purpose, 31 rabbits were distributed into: control group (CG, n = 10), continuous wave laser group (GLC; n = 10) and pulsed wave laser group (GLP; n = 11). Postoperative management was similar between all groups, with the exception of laser application, as indicated by the group. The GLC and GLP groups showed similar evolution, with a satisfactory healing process of the graft, unlike the GC group. These results were maintained in the microscopic evaluation, as the groups treated with laser showed less inflammation, better integration with the receptor area, greater re-epithelialization and collagenization. There was no difference in vascular density between the treatment groups on immunohistochemical analysis. The newly created wound was not able to provide nutrition for the skin graft in rabbits, but LIL is an efficient adjuvant therapy in stimulating healing between the recipient area and the graft, promoting full integration. However; although, statistically there was no difference in the form of light emission, pulsed or continuous, patients who received continuous wave LIL showed superior microscopic evolution.
Comparação entre as ondas contínua e pulsada do laser de baixa intensidade na cicatrização de enxertos cutâneos aplicados em feridas recém-criadas de coelhos (Oryctolagus cuniculus)
Keywords: cicatrization; exergy; laser therapy; rabbit